Reactivity of fluorographene is triggered by point defects: beyond the perfect 2D world - Medveď, Miroslav; Zoppellaro, Giorgio; Ugolotti, Juri; Matochová, Dagmar; Lazar, Petr; Pospíšil, Tomáš; Bakandritsos, Aristides; Tuček, Jiří; Zbořil, Radek; Otyepka, Michal (Nanoscale, 2018)
Preparation of graphene derivatives using fluorographene (FG) as a precursor has become a key strategy for the large-scale synthesis of new 2-D materials (e.g. graphene acid, cyanographene, allyl-graphene) with tailored physicochemical properties. However, to gain full control over the derivatization process, it is essential to understand the reaction mechanisms and accompanying processes that affect the composition and structure of the final products. Despite the strength of C-F bonds and high chemical stability of perfluorinated hydrocarbons, FG is surprisingly susceptible to reactions under ambient conditions. There is clear evidence that nucleophilic substitution on FG is accompanied by spontaneous defluorination, and solvent-induced defluorination can occur even in the absence of any nucleophilic agent. Here, we show that distributed radical centers (fluorine vacancies) on the FG surface need to be taken into account in order to rationalize the defluorination mechanism. Depending on the environment, these radical centers can react as electron acceptors, electrophilic sites and/or cause homolytic bond cleavages. We also propose a new radical mechanism of FG defluorination in the presence of N,N'-dimethylformamide (DMF) solvent. Spin-trap experiments as well as 19F NMR measurements unambiguously confirmed formation of N,N'-dimethylformyl radicals and also showed that N,N'-dimethylcarbamoyl fluoride plays a key role in the proposed mechanism. These findings imply that point defects in 2D materials should be considered as key factor determining their chemical properties and reactivity.